Penggunaan Vidio Animasi sebagai Media Edukasi Untuk Mencegah Anemia Pada Kehamilan - Susindra, Yoswenita; Dewi, Riskha Dora Candra; Satya, Malinda Capri Nurul (P3M Politeknik Negeri Jember, 2024)
Pregnancy anemia is a global public health issue and this condition contributes to morbidity and mortality rates among women. 42% of pregnant women worldwide experience anemia. In Jember, East Java, the coverage of pregnant women receiving iron supplement tablets is 88.6% of the total pregnant womens. A health knowledge questionnaire given to respondents in the Sumbersari and Kaliwates areas revealed that most respondents' knowledge about pregnancy anemia is still low. A community service activity on